Implementasi Sarana Prasarana Esensial Terhadap Kurikulum Merdeka Anak Usia Dini : Implementation of Essential Infrastructure Facilities for Early Childhood Independent Curriculum - utami-kumala-dewi; Hibana; Nurhusni Kamil; Fadila Arnisa Harahap; Faiqatuz Zahrah (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
The era of entering the industrial revolution 5.0, education is closely related to world attention regarding an institution, especially early childhood education. The success of the learning process of an institution is supported by the availability of adequate essential infrastructure facilities according to the applicable curriculum. The independent curriculum is a curriculum that applies in Indonesia with a fun learning orientation centered on students, as well as the creativity of educators in providing a variety of learning to be the main factor in achieving the learning process. Freedom of learning does not prioritize Calistung learning (Read, Write, Count), and is centered on LKA (Children's Worksheets). Therefore, the researcher is interested in examining more deeply the implementation of infrastructure for the independence curriculum at Pangudi Luhur Jenarwetan Kindergarten. Researchers used qualitative research methods that are descriptive analytic by collecting data through observation, documentation and interview techniques. The results of this study are the implementation of infrastructure that has been used during the learning process using an independent curriculum, one of which uses natural materials. Â  ABSTRAKÂ  Era memasuki revolusi industri 5.0 pendidikan erat kaitannya dari perhatian dunia mengenai suatu lembaga khususnya pendidikan anak usia dini. Keberhasilan proses pembelajaran suatu lembaga didukung dengan tersedianya sarana prasarana esesnsial yang memadai sesuai kurikulum yang berlaku. Kurikulum merdeka merupakan kurikulum yang berlaku di Indonesia dengan berorientasi pembelajaran yang menyenangkan berpusat pada peserta didik, serta kreativitas pendidik dalam menyediakan ragam pembelajaran menjadi faktor utama tercapainya proses pembelajaran. Merdeka belajar tidak mengutamakan pada pembelajaran Calistung (Baca, Tulis, Hitung), dan berpusat pada LKA (Lembar Kerja Anak). Maka dari itu, peneliti tertarik untuk mengkaji lebih dalam tentang implementasi sarana prasarana terhadap kurikulum merdeka di TK Pangudi Luhur Jenarwetan. Peneliti menggunakan metode penelitian kualitatif bersifat deskriptif analitik dengan pengumpulan data melalui teknik observasi, dokumentasi dan wawancara. Hasil dari penelitian ini berupa implementasi sarana prasarana yang telah digunakan selama proses pembelajaran menggunakan kurikulum merdeka, salah satunya menggunakan bahan alam.